Conservative management of thyroglobulin‐positive, nonlocalizable thyroid carcinoma. Issue 2 (1st June 2013) - Frank, Robert W.; Middleton, Laura; Stack, Brendan C.; Spencer, Horace J.; Riggs, Ann T.; Bodenner, Donald L.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to demonstrate a role for observation of patients with differentiated thyroid cancer (DTC) with persistent, nonlocalizable disease. Methods Our study was conducted on outpatients seen at our institution from 1999 to 2009 having total thyroidectomy, radioactive iodine (RAI) ablation, measurable serum thyroglobulin (Tg), and no evidence of disease on whole body or positron emission tomography (PET) scans. Results Nineteen patients in our study group aged 20 to 73 with an average follow‐up of 5.5 years (range, 2–12 years); all were treated with postoperative RAI (99–210 mCi, average 119). Mean Tg ranged from 0.41 to 4.34. Tg levels remained stable or gradually decreased in all patients. Conclusion After total thyroidectomy and RAI therapy, patients may present with mildly elevated Tg values without localizable disease. These patients may have additional RAI treatments based on the Tg elevation. However, our clinical experience has shown that many of these patients will have Tg levels that either achieve stability or decrease over time without further treatment. © 2013 Wiley Periodicals, Inc. Head Neck 36: 155–157, 2014